ANALISIS PENERAPAN PRINSIP FIFO (FIRST IN, FIRST OUT) DALAM OPTIMALISASI TATA LETAK GUDANG FARMASI : STUDI KASUS PENINGKATAN LOGISTIK DI RSI METRO - Lestari, Rizky Aprilianti; Putra, Yogi Catur; Handayani , Melan (LPPM Universitas Awal Bros, 2025)
This study aims to address the challenges in managing the pharmaceutical warehouse at Metro Islamic Hospital (RSIM), which has not fully complied with the First In, First Out (FIFO) principle. This non-compliance has the potential to cause a buildup of expired stock, financial losses, and decreased operational efficiency, as well as endangering patient safety. This report is the result of Field Learning Practice (PBL) conducted at RSIM, identifying the causes of the problem and evaluating its impact.. Method: The approach used in this study was direct observation of the storage and arrangement of pharmaceutical supplies in the RSIM warehouse. Data was collected through field observations, interviews with relevant staff, and internal document analysis. Priority issues were identified using the USG (Urgency, Seriousness, Growth) method to determine the main issues that needed immediate attention.. Conclusion: The results of this study indicate that the issue of drug arrangement that does not comply with FIFO is a top priority. Implementing a strategy to improve the layout of the pharmaceutical warehouse based on FIFO at RSIM is crucial to minimize the risk of expired drugs, reduce financial losses, improve patient safety through timely and high- quality drug administration, and enhance compliance with good pharmaceutical practice (GPP) regulations.Keyword: Pharmaceutical Warehouse, FIFO, Metro Islamic Hospital, Operational Efficiency, Patient Safety.